ON AUTOMATED QUALITY CONTROL OF GEOPHYSICAL WELL LOGGING DATA - Roman Victorovich Pelmegov; Artem Georgiyevich Kudelin (Advanced Engineering Research, 2014)
The development of scientific principles, methods, and techniques of the automated control of the primary data recorded in the geophysical well logging is considered. The issue of termination of logging on a particular well is often associated with subjective expert assessments. The need for automated detection of errors and quality control of the recorded data during or immediately upon completion of studies is discussed. A brief analysis of the unreliability symptoms of record fragments is provided. An algorithm using iterative modeling techniques of incomplete data with low-dimensional manifolds for solving the problem of assessing the quality of the well logging data is proposed. Examples demonstrating the high efficiency of the iterative modeling methods for incomplete data using low-dimensional manifolds in the problem of space filling of geophysical study data are given; and the results of the numerical experiments on solving the problem of data quality control of electric logging are provided.